The Severn Wildfowl Trust expedition to central Iceland, 1951 - Scott, Peter; Fisher, James; Guomundsson, Finnur (Wildfowl, 1952)
A party of four assisted by Icelandic farmers spent five weeks (between 28 June and 2 August 1951) at what may prove to be the world’s largest breeding colony of Pink-footed Geese (Anser brachyrhynchus). The history of this and other breeding colonies is outlined. The colony is in an oasis at the south-east side of the Hofsjkul in the centre of Iceland at a height of 2000 feet. Studies were mainly concentrated on marking, with a view to population measurement, and on behaviour. It was estimated that there were probably about 2300 nests in the oasis and that the population including adults and goslings may have been of the order of 13,000 birds. Recaptures of marked birds were used in making these estimates. Food, predation, nests, eggs and goslings, behaviour of parents and broods are described and discussed. Methods of capture were discovered which throw light on the functions of ancient ruined ’goose-folds’ found in the area. Five large drives were made, in one of which 267 geese were caught. During the whole period 1151 geese and goslings were marked, some with Swedish-type wing-tags. A list with notes on status and behaviour of thirty-two species of birds seen in the oasis is followed by notes on invertebrates, flowering plants and hot springs.